Socio-cultural determinants of maternal health care seeking behaviour in Seme side of Benin Republic (2013)
Research on maternal health was conducted among the residents of the Seme border community in republic of Benin to determine the available maternal health care services in the community and the level of accessibility to residents, to find out the pattern of the maternal health care seeking behavior and to examine the relationships between the socio-cultural characteristic and maternal health care seeking behavior in the area. The major instruments used were structured questionnaire, key informant interview and non-participant observation method. The study established that there are a considerable number of maternity hospitals and health centers in the community, many of which are privately owned. Residents tend to have a terrible level of access to the maternity services as there is no enough publicity either through word of mouth referrals or information from social service workers. The study also discovered that a very large proportion of the resident of the area use both the western maternal health care services and traditional substances. Due to the setting of this border area, a central cultural connotation is not prominent; hence the cultural influence on the maternal health seeking behavior is not general to the society as a whole. Though many residents use the western (private and public) service, factors like husbands approval, money for treatment, and personal cultural preferences still had negative effects on the maternal health seeking behavior in the area.